A new protocol toward high output TENG with polyimide as charge storage layer. (August 2017) - Feng, Yange; Zheng, Youbin; Zhang, Ga; Wang, Daoai; Zhou, Feng; Liu, Weimin
Abstract: A new structured triboelectric nanogenerators (TENG) was designed by adding a transition layer between the friction layer and the conduct layer, which could significantly improve the output performance by one order of magnitude. The material of transition layer, such as polyimide, has high ability to store the triboelectrification charges, resulting in more induced charges and higher external current. After adding a polyimide charge storage layer with the thickness of 25 µm, the short-circuit current and output voltage of polyvinylidene fluoride (PVDF) and nylon (NY) based TENG (Cu-PI-PVDF@NY-Cu) increased from 9.2 μA to 65 μA, and 110 V to 1010 V, respectively. The maximum charge density can reach approximately 105 μC/m 2 with the maximum value of the output power of 5.87 mW under 4 MΩ loading resistance, which can instantaneous light up 992 commercial LEDs and charge a capacitor with the speed increased by 10 times. Moreover, the mechanism and influence factors including the surface structure, composition and thickness of the charge keeping layer to enhance the output of TENGs were discussed in detail. The charge decay tests of the transition layers showed that polyimide layer has very good charge keeping ability with a decay rate of only about 20% in 4 h, while the charge of PVDF decrease about 97% in 4 h, which is a key factor for its lower output. Graphical abstract: A new protocol toward high output triboelectric nanogenerator was introduced by adding a transition layer as the charge storage layer. Due to the charge retention property, the TENG with PI charge storage layer obtains a high short-circuit current and output voltage values of 65 μA and 1010 V, respectively. This study gives some guidance for choosing materials as charge storage layer to improve the output of TENGs, which paves a route to drive the practical applications of TENGs in energy harvesting, self-powered sensors, and so on. Highlights: The output of PVDF and Nylon based TENG was highly enhanced by adding an PI transition layer. The thickness, morphology, polarity and charge decay property of transition layer play important roles in TENG's output. The TENG with PI transition layer achieves a peak V o of 1010 V and I sc of 65 μA.